The Estimation of a Joint Wage-Hours Labor Supply Model - Moffitt, Robert (Journal of Labor Economics, 1984)
In this paper the standard cross-sectional static model of labor supply is modified to make the wage endogenous, and a joint wage-hours model is estimated. The econometric technique addresses the non-linearity of the budget constraint by approximating the constraint by a series of discrete points. The results show that the budget constraint is indeed nonlinear, that hours affect the wage quadratically, that true wage elasticities are lower as a result, and that the model fits the hours distribution much better than the standard Tobit model.